PERAN ROHIS DALAM PENINGKATAN MOTIVASI SISWA BELAJAR AGAMA ISLAM DI SMA NEGERI 2 SRAGEN - WIDYAWATI , FITRI AGUSTIN (2011)
The last few years often we see the brawl between the schools, conflict amon childrens which resulted in fights and killings, excessive juvenile delinquency students are considered rude, not responsible for their actions, and also man students who become of drug addicts. Rohis as one part of self development i public schools. When the role Rohis can influence students to develop itself into personal love of his religion then grow students who not only put their favorit world are only just messing around, who do not pay attention to his role for th benefit of society. Rohis role in public schools when it can give contribute t motivate students to study Islamic religion to make students who could use the youth by not worth useless. Purpose of this research is to know Rohis role i increasing student motivation to study religion in SMA Negeri 2 Sragen and t find strategies that do Rohis in increasing motivate students to study abou religion in SMA Negeri 2 Sragen. This research is qualitative because the natur of the data collected, which is patterned descriptive words written or spoken of th people and the perpetrators were observed. This study also investigated the fiel (Field Research) as a method to collect qualitative data. Method of data analysi with data reduction, data presentation and data verification. Based on the researc result abaout Rohis role in student motivation to learn increasing Islam in SMA Negeri 2 Sragen: (1) Including views of the religious conditions of students ar already quite good and quite varied forms of activity Rohis. Response from teachers about the activities of Islamic Education Rohis already advanced an supports the advancement of Islam in SMA Negeri 2 Sragen while the student responses as follows Rohis to seek knowledge. The students that do not atten Rohis give opinion that Rohis role in student motivation to learn increasing Islam in SMA Negeri 2 Sragen. (2)The strategy that used to increase its role in th coordination of them with Rohis organization, in cooperation with the schoo especially with the Islamic Religious Education teachers, and cooperation with th alumni.